Thermodynamics of Surface Phenomena - Dadashev , Raykom Kh author (New Delhi : Viva Book, 2017)
The book is concerned with the main assumptions of the theory of Gibbs capillarity theory and fundamental thermodynamic equations, derived by the method of the finite thickness layer. Special attention is given to applied aspects of the thermodynamic theory of surface phenomena. Methods for calculating adsorption in multicomponent solutions are examined in detail. Systems of equations for calculating adsorption in real multicomponent systems from the concentration dependence of surface tension are derived for the first time. Experimental data on surface tension and density in binary and multicomponent systems are presented. Analysis of the results is used to develop methods for predicting the surface properties of multicomponent systems from the data on the properties of binary melts.
Includes appendix, references and index
Keywords: Thermodynamics; Surface chemistry; Interfaces; Surface tension; Physical chemistry